2019
DOI: 10.1016/j.cose.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

When Human cognitive modeling meets PINs: User-independent inter-keystroke timing attacks

Abstract: This paper proposes the first user-independent inter-keystroke timing attacks on PINs. Our attack method is based on an interkeystroke timing dictionary built from a human cognitive model whose parameters can be determined by a small amount of training data on any users. Our attacks can thus be potentially launched in a large scale in real-world settings. We investigate inter-keystroke timing attacks in different online attack settings and evaluate their performance on PINs at different strength levels. Our ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…Examples of Inter-keystroke Timing Sequences (in ms) for PIN Entry Tasks can be a serious threat to users relying on such PINs. For instance, Liu et al [19] proposed a user-independent inter-keystroke timing attack on PINs that performed significantly better than random guessing attacks. The attack methodology relies on an inter-keystroke timing dictionary built from Fitts's Law, which relies on conducting real human user study to derive parameters of this model.…”
Section: Modeling Six-digit Pin Entriesmentioning
confidence: 99%
See 3 more Smart Citations
“…Examples of Inter-keystroke Timing Sequences (in ms) for PIN Entry Tasks can be a serious threat to users relying on such PINs. For instance, Liu et al [19] proposed a user-independent inter-keystroke timing attack on PINs that performed significantly better than random guessing attacks. The attack methodology relies on an inter-keystroke timing dictionary built from Fitts's Law, which relies on conducting real human user study to derive parameters of this model.…”
Section: Modeling Six-digit Pin Entriesmentioning
confidence: 99%
“…A total of 50 different 6-digit PINs were used in the real human user study conducted by Liu et al [19]. Each PIN was entered using the number pad as illustrated in Figure 5(b).…”
Section: Modeling Pin Entriesmentioning
confidence: 99%
See 2 more Smart Citations
“…To protect this private data from unauthorized access, traditional explicit authentication methods for mobile devices are employed using a password, personal identification number (PIN), face, fingerprint, or secret pattern. Previous work has shown that such solutions provide limited security because of several reasons [2][3][4][5]. Firstly, they make devices vulnerable to guessing, shoulder surfing, smudge, and spoofing attacks.…”
Section: Introductionmentioning
confidence: 99%